2009
DOI: 10.1016/j.ygeno.2009.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Identification of microRNA in the protist Trichomonas vaginalis

Abstract: MicroRNAs (miRNAs) are a class of small noncoding RNAs that have important regulatory roles in multicellular organisms. However, miRNA has never been identified experimentally in protist. Direct cloning of 438 expressed miRNA tags by microRNA serial analysis of gene expression from the parasitic protist Trichomonas vaginalis identified nine candidate miRNAs. Bioinformatics analysis of the corresponding genomic region revealed that these miRNA candidates contain a classical stem-loop-stem structure of pre-micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(40 citation statements)
references
References 52 publications
1
38
0
1
Order By: Relevance
“…This flagellate can use small nucleolar RNA as miRNA precursor (Saraiya and Wang 2008). We demonstrated that T. vaginalis have a functional miRNA regulatory machinery in our previous work (Lin et al 2009). However, because the lack of commercially available antibodies to follow the changes of miRNAs targets predicted insilico at protein level, it is almost impossible to perform any in-depth analysis for miRNA targets and their functions.…”
Section: Introductionmentioning
confidence: 52%
See 2 more Smart Citations
“…This flagellate can use small nucleolar RNA as miRNA precursor (Saraiya and Wang 2008). We demonstrated that T. vaginalis have a functional miRNA regulatory machinery in our previous work (Lin et al 2009). However, because the lack of commercially available antibodies to follow the changes of miRNAs targets predicted insilico at protein level, it is almost impossible to perform any in-depth analysis for miRNA targets and their functions.…”
Section: Introductionmentioning
confidence: 52%
“…The difference between the mRNA and protein expression levels implied that miRNAs may inhibit the translation of this gene. Potential miRNA-binding sites in the full length Tv_MDH mRNA was screened by using the miRNA target detection program, RNA22 (Miranda et al 2006) against the miRBase V13 (Griffiths-Jones et al 2008) and nine T. vaginalis novel miRNA candidates (tva-miR-001∼9, have been submitted to miRBase) that we identified in our previous study (Lin et al 2009). The full length Tv_MDH mRNA (GQ202975) obtained by clustering of EST sequences downloaded from TvXpress Database and The secondary stem-loop-stem structure and expression level of tva-miR-1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The expression of Tv-AGO1 (TVAG-453810) and Tv-AGO2 (TVAG-411040) genes were determined by quantitative real-time PCR, suggesting that functional miRNA machinery exists in T. vaginalis. Thereafter, a total of nine tva-miRNA (tva-miR-001∼009) ranging from 17 to 23 nucleotides long have been identified using direct cloning of miRNA tags and bioinformatics analysis (Lin et al 2009). However, the exact length of the cloned miRNAs in T. vaginalis, target prediction and miRNA-target interaction are not yet known.…”
Section: Mirnas In Protozoan Parasitesmentioning
confidence: 99%
“…approaches and molecular cloning. The most recent release of the miRNA database, miRBase release 18.0, contains over 18,000 miRNAs in animals, plants, viruses, and even in some unicellular organisms (Griffiths-Jones et al 2006;Zhao et al 2007;Sunkar et al 2008;Lin et al 2009;Zhu et al 2009). The unicellular organisms have been shown to encode miRNAs, which suggested that the miRNA pathway is an ancient mechanism of gene regulation, and may have originated prior to the emergence of multicellularity (Zhao et al 2007).…”
Section: Introductionmentioning
confidence: 99%